HRP2 and PLDH Performance Comparison as Rapid Diagnostic Tools for Symptomatic Malaria Patients at Rugazi HC IV in Rubirizi District - Anitah, Nakavuma; Afrika, Musau Immanuel; Hassan, Lumu; Rose, Atimaaku Palma; Evalyne, Ankunda; Bosco, Agaba; Benson, Okongo; Rogers, Kalyetsi; Frank, Ssendyabane; Enock, Muwanguzi; Bagenda, Charles Nkubi; Rugera, Simon Peter (International Internal Medicine Journal, 2024)
Background: Rapid and precise laboratory diagnosis is essential for effectively diagnosing and managing malaria patients. Malaria rapid diagnostic tests (mRDTs) play a critical role in malaria diagnosis in resource-constrained settings with limited access to labs and trained staff. The efficiency of two mRDTs (HRP2 and pLDH) was compared against microscopy, the gold standard for malaria diagnosis, in this study. Methods: In a cross-sectional study, 308 participants were tested for malaria parasites using two mRDTs and blood smear microscopy as the gold standard. STATA software version 17 was used for data analysis. Results: Out of the 308 participants, 82 tested positive for HRP2 mRDT (26.62% (95% CI: 21.97-31.86) positivity rate, 73.38% (95% CI: 68.14-78.83) negativity rate), and 99 tested positive for pLDH mRDT (32.14% (95% CI: 27.14-37.59) positivity rate, 67.86% (95% CI: 62.41-72.86) negativity rate). Using microscopy as the gold standard, the sensitivity, specificity, PPV, and NPV were determined. For HRP2 mRDT, sensitivity was 77.78% (95%CI: 73.13-82.42), specificity 97.61% (95%CI: 95.90 - 99.31), PPV 93.90% (95%CI: 91.23 – 96.56), and NPV 90.27% (95%CI: 86.96-93.58). For pLDH mRDT, the sensitivity was 94.95% (95% CI: 92.50-97.40), specificity was 97.61% (95% CI: 95.90-99.31), PPV was 94.95% (95% CI: 92.50 – 97.40), and NPV was 97.61% (95% CI: 95.90 - 99.31). The dominant malaria species was Plasmodium falciparum (74.7%), followed by Plasmodium vivax (12.1%) and Plasmodium ovale (1%). Mixed infections of plasmodium falciparum and plasmodium vivax (7.1%) and plasmodium falciparum and plasmodium ovale (5.1%) were also observed. Conclusion: There was no significant difference in the positivity rate, negativity rate, specificity or PPV in both mRDTs. However, a significant difference in the NPV and sensitivity of HRP2 and pLDH mRDTs was observed where HRP2’s sensitivity was below the WHO recommendation of ≥95% in this study population; thus, there is a need to improve the sensitivity of this mRDT kit. In our study, most malaria infections were caused by Plasmodium falciparum, followed by P. vivax and P. ovale.
Keywords: Malaria Rapid Diagnostic Tests; Malaria Microscopy; Symptomatic Infections